SMIIC Forum 2012 - Kayadibi, Saim (Association of Muslim Social Scientists, 2013)

(untitled)
Organized by the Standards and Metrology Institute for Islamic Countries (SMIIC), a subsidiary organ of the Organization of Islamic Cooperation (OIC), this forum was held on November 6-9, 2012, at Turkey’s Cornelia De Luxe Resort in Belek. The 160 delegates, who came from thirty-five countries, represented the National Standardisation Bodies (NSB), important national organizations of member countries, and such international organizations as the International Organisation for Standardisation (ISO), the International Electrotechnical Commission (IEC), the European Committee for Electrotechnical Standardisation (CENELEC), the Standardisation Organisation for the Cooperation Council for the Arab States of the Gulf (GSO), the Turkish Standards Institution (TSE), the Turkish Accreditation Agency (TURKAK), the Saudi Standards Metrology and Quality Organization (SASO), the Malaysian National Metrology Laboratory (SIRIM), the International Laboratory Accreditation Cooperation (ILAC), the OIC General Secretariat, the Commercial Cooperation of the Organization of Islamic Cooperation (COMCEC), the Statistical Economic and Social Research and Training Centre (SESRIC), and the Islamic Centre for the Development of Trade (ICDT).